IMPLEMENTASI PERATURAN DAERAH NO 1 TAHUN 2013 TENTANG PANDAI MEMBACA AL-QUR’AN DI KECAMATAN BANGKINANG KOTA KABUPATEN KAMPAR - Susanto, Adhi; ", Sujianto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Implementation is derived from the English language is to implement the means to implement. Implementation is the provision of means to implement something that impacts or due to something. Something was done to impact or it may be due to laws, regulations, judicial decisions and policies made by government agencies in the state life. Implementation of local regulation No. 1 of 2013 on Smart Reading Al-Quran and outs of running with the maximum as expected yank Kampar regency government. The purpose of these regulations is to make the public Kampar religion makes people high-value, particularly the District Bangkinang City.Theoretical concept used by the author is the Policy and Program Implementation. Researchers use qualitative research with descriptive study. In collecting the data, the writer used interview and observation techniques. Authors use informants as sources of information and techniques triagulasi as a source of data authenticity.Implementation of Regional Regulation No. 1 Year 2013 About Smart Reading Al-Quran in District Bangkinang City Kampar regency has not gone up, it proved there are still many schools that have not implemented these programs and there are still many people who do not know about the program Smart Reading Al -Quran. Factors that affect the implementation of the Regional Regulation No. 1 On good at reading the Koran in the district are the Kampar regency Bangkinang Public Participation Fund / Cost and Infrastructure in mengimplementasian the Regulation.Keywords: Implementation, Program and Local Regulations